Coadapting multidimension process properties. Issue 11 (24th March 2017) - Khelladi, Djamel Eddine; Bendraou, Reda; Hebig, Regina; Gervais, Marie‐Pierre
Abstract: In the last decades, process verification has been intensively addressed and has become an essential activity to correct and to remove errors before process execution. Typical process verification ecosystems propose to express properties to be verified on the process. A property expresses a desired behavior that must hold or not in the process execution. Processes during their lifespan are continuously adapted for several purposes: enriching, correcting, and refactoring the process. When a process is adapted, the existing properties must naturally be rechecked to ensure that no errors have been introduced, ie, the properties still hold. However, the properties may become outdated and must be coadapted w.r.t. the adapted process before to be rechecked. Otherwise, the verification may raise false alarms or may not detect newly introduced errors. In this paper, we propose a coadaptation approach of properties while considering process adaptation for the different dimensions, namely, control flow, object flow, resources, and timing. We systematically studied process changes in the multiple dimensions to identify those that do impact properties and for which we propose resolution strategies. Our preliminary evaluation shows that our resolutions strategies allow to support users in correctly coadapting impacted properties. Abstract : As processes evolve, so must process properties to remain up‐to‐date and usable by verification tools. This holds for properties of different process dimensions, namely, control flow, object flow, resources, and timing. Our research highlights that properties may indeed become obsolete after process adaptation and that with the knowledge of process adaptation changes, the specified properties can be coadapted semiautomatically. We also noticed that alternative resolutions can be used to coadapt the process properties.